KECEPATAN REAKSI DAN DAYA LEDAK OTOT TUNGKAI BERKONTRIBUSI TERHADAP KEMAMPUAN FOOTWORK BULUTANGKIS - Eval Edmizal; Donie Donie; Vega Soniawan (Jurnal Sporta Saintika, 2020)
Based on Researchers field observation, it has found out that students who have taken Advance Badminton Course, haven’t had a good footwork ability. This research is aimed to find out the relationship among reaction speed, limb muscle explosive,towards footwork ability achievement. This research is a correlational research, and the population of this research is all of 30 students who have taken advance badminton course in Sport Science Faculty of Universitas Negeri Padang. Research instruments of this research are whole body reaction for speed reaction, standing board jump for limb muscle explosive and t-test for agility. Data analysis shows that (1) reaction speed has significant contribution toward footwork ability for students who have taken Advance badminton Course in Sport Science Faculty Padang StateUniversity, its contribution is 14,88%. (2) limb muscle explosive has significant contribution toward the students’ foot work ability, the contribution is 33,67%.